Development of a new highly sensitive and selective spectrophotometric method for the determination of selenium at nano-trace levels in various complex matrices using salicylaldehyde-orthoaminophenol - Ahmed, Muhammad Jamaluddin; Uddin, Muhammad Jihan; Hoque, Muhammad Emdadul (European Journal of Chemistry, 2021)
A new spectrophotometric reagent, salicylaldehyde-orthoaminophenol (Sal-OAP) has been synthesized and characterized for the determination of selenium through novel reaction techniques. Also, a new highly selective, and sensitive spectrophotometric method for the nano-trace determination of selenium using salicylaldehyde-orthoaminophenol (Sal-OAP) has been developed. Sal-OAP undergoes reaction in a slightly acidic solution (0.0001-0.0002 M H2S04) with selenium (IV) to give an orange-red chelate, which has an absorption maximum at 379 nm. The reaction is instantaneous and absorbance remains stable for over 24 h. The average molar absorption co-efficient and Sandell’s sensitivity were found to be 6.4×105 L/mol.cm and 1.0 ng/cm2 of, respectively. Linear calibration graphs were obtained for 0.001-40.000 mg/Lof Se having detection limit of 0.1 µg/L and RSD 0-2 %. The stoichiometric composition of the chelate is 1:2 (Se:Sal-OAP). A large excess of over 60 cations, anions and some common complexing agents, such as chloride, azide, tartrate, EDTA, SCN¯etc., do not interfere in the determination. The developed method was successfully used in the determination of selenium in several Certified Reference Materials (Alloys, steels, human urine, bovine liver, drinking water, tea, milk, soil, and sediments) as well as in some environmental waters (Potable and polluted), biological fluids (Human blood, urine, hair, and milk), soil samples, food samples (Vegetables, rice, and wheat) and pharmaceutical samples (Tablet and syrup) and solutions containing both selenium (IV) and selenium (VI) as well as complex synthetic mixtures. The results of the proposed method for assessing biological, food and vegetables and soil samples were comparable with ICP-OES and AAS were found to be in excellent agreement. The method has high precision and accuracy (s = ±0.01 for 0.5 mg/L).